Pengembangan Desa Wisata Mini Rafting Jurang Sate - Muh Husein Baysha; Endah Resnandari Puji Astuti; Noor Akhmad (Sasambo: Jurnal Abdimas (Journal of Community Service), 2019)
The purpose of this community service activity is to develop a mini rafting vehicle for satay cliff tourism as a tourist attraction which has an impact on improving the economy of the people of the village of Soccerek Pringgarata, Central Lombok. Mini rafting satay gorge as a means of promotion, sports, recreation to attract tourists so that it fosters the economy of the soccer village community. The method of implementing activities is the community development method, which is an approach in community development activities where the community is directed to achieve better social, economic and cultural conditions and the Participatory method of implementation steps, namely Problem posing, problem analysis, problem determination objectives (objectives) and objectives (objectives), actions plans (action planning), the stage (implementation) of the implementation of activities and evaluation (evaluation). The material provided in this training and assistance includes 1) introduction of rafting equipment; 2) basic rafting techniques; 3) rescue rafting; 4) practice of using rafting equipment; 5) the practice of rescue rafting. 25 participants took part in the training and mentoring activities. The results of the training and assistance of mini rafting and rescue rafting showed that as many as 84% of participants understood "mini rafting" and 80% of participants understood "rescue rafting". Activities of structuring the Jurang Sate Tourism Area, PPIP IKIP Mataram Team in partnership with the Youth Organization "Duta Taruna", Pokdasrwis "Kanak Jarin", and Bumdes "Sahara Jaya" in the Village of Soccer, Pringgarata District, Central Lombok. Implementation of the arrangement of this tourist area also involves the people of the Village of Soccer to work together to organize the tourist area and prepare for the opening of a mini rafting vehicle.